MICROBIAL DIVERSITY OF MOISTURE STRESS TOLERANT RHIZOBACTERIA ASSOCIATED WITH SORGHUM AND ALLIED WEEDS DURING SORGHUM CROP PRODUCTION UNDER DROUGHT CONDITION - KALINDEE S. SHINDE,; S. G. BORKAR, (The Bioscan, 2024)
In the present investigation the microbial diversity particularly bacteria in the moisture stress (drought) soil environment depends on the types of host plant root on which these bacterial type colonize have been studied. Total 81 bacterial colonies isolated from sorghum and allied weed plants viz, Cassia cerassia, Fimbristylis miliacea, Argemone mexicana, Chrozophoro rottleri, Fumaria parviflora and Euphorbia esula using NA media. Out of which 42 were obtained as root endophytic isolates whereas 39 isolates were obtained as root ectophytic isolates. All these endophytic and ectophytic bacterial culture were able to grow in in vitro condition at 13% soil moisture level indicating that they sustain the severe drought condition in soil. From this work it can be concluded that these moisture stress tolerant bacteria would be present and sustain under drought stress condi tion.